PVC Based Ion-Exchange Membrane Blended with Magnesium Oxide Nanoparticles for Desalination: Fabrication, Characterization and Performance - Parvizian, F.; Sadeghi, Z.; Hosseini, S. M. (Journal of Applied Membrane Science & Technology, 2017)
In this study, polyvinyl chloride (PVC) based nanocomposite cation exchange membranes incorporated with magnesium oxide (MgO0 nanoparticles were fabricated by nonsolvent induced phase inversion method. The additive concentration and electrolyte conditions (concentrations/pH) were investigated. Morphology studies were done using SOM and SEM images exhibited uniform distribution of MgO nanoparticles in the membrane structure. FTIR analysis showed the chemical structure of prepared membrane that demonstrated MgO nanoparticles presence. The hydrophilicity of membranes increased when 0.5-4.0 wt.% of additive were embedded into the polymer matrix. The transport characteristics of prepared membrane were improved by increasing nanoparticle content from 0.5 to 1 wt.%. It was demonstrated that the ionic flux of developed cation exchange membranes improved with an increase in additive content up to 1 wt.%. A considerable reduction was observed in the values of electrical resistance for the prepared membrane containing MgO nanoparticles. Ionic selectivity was enhanced at the more concentered solution and was slightly decreased at higher electrolyte concentration. Moreover, at the electrolyte solution of pH7 the optimal transport properties were achieved for the membranes.